2020
DOI: 10.3389/fvets.2020.00265
|View full text |Cite
|
Sign up to set email alerts
|

Use of Reticulated Hyaluronic Acid Alone or Associated With Ozone Gas in the Treatment of Osteoarthritis Due to Hip Dysplasia in Dogs

Abstract: This study aimed to evaluate reticulated hyaluronic acid alone or associated with ozone gas in the treatment of osteoarthritis due to hip dysplasia in dogs. Fourteen client-owned dogs were randomly assigned into two groups: Group 1-single intra-articular injection of hyaluronic acid; Group 2-single intra-articular infiltration injection of hyaluronic acid associated with ozone gas. Each hip joint received an average of 0.75 mL of reticulated hyaluronic acid ultrasound-guided. Ozone gas at a dose of 45 µg/mL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In the United Kingdom alone, 200,000 new cases of OA are diagnosed in dogs annually, with both external (injury, obesity, age) and genetic factors contributing (1,4,5). At present, the disease is treated symptomatically by regularly administering non-steroidal anti-inflammatory drugs or by repeated injections of hyaluronic acid (6,7). Surgical solutions such as arthrodesis or excision arthroplasty (e.g., total joint replacement) are also used in more severe cases (8).…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom alone, 200,000 new cases of OA are diagnosed in dogs annually, with both external (injury, obesity, age) and genetic factors contributing (1,4,5). At present, the disease is treated symptomatically by regularly administering non-steroidal anti-inflammatory drugs or by repeated injections of hyaluronic acid (6,7). Surgical solutions such as arthrodesis or excision arthroplasty (e.g., total joint replacement) are also used in more severe cases (8).…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal experiments have shown that hip dysplasia and other joint abnormalities may be a consequence of hyaluronic acid deficiency in synovial fluids [45] [46]. It has also been shown that the intra-articular hyaluronic acid implementation alone or associated with ozone allowed improvement of hip dysplasia in animal model [47]. The role of hyaluronic acid is found to be crucial according to both regression models describing the connection between innate immunity and connective tissue as well as between some connective tissue parameters.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, recent advances have suggested a novel therapy with anti-nerve growth factor monoclonal antibodies as a replacement for traditional analgesics [ 120 , 121 ]. Furthermore, intra-articular administration of hyaluronan [ 122 , 123 ], corticosteroids [ 122 ], platelet-rich plasma [ 124 ], or ozone gas [ 123 ] are also considered an alternative when controlling joint pain and inflammation. In addition, the wide range of early mechanical conservative options available in humans, lack in dogs.…”
Section: Main Textmentioning
confidence: 99%